Phone Number Verification sebagai MFA (Multi-Factor Authentication) Solusi Keamanan Verifikasi Identitas Berbasis SIM Card - Puji Suharmanto; Sri Endang Wahyuni (Navigation Physics : Journal of Physics Education, 2023)
Post-Pandemic and Industry 4.0 era accelerates the change of community trends, especially in how to pay when transactions of goods and services are increasingly cashless, increasingly online shopping activities with e-commerce to public service and business processes that are increasingly optimizing digital adoption. The digital security process is very fundamental today because it is very vulnerable to malware attacks, hackers to social engineering to seize accounts from the original owner. Today's digital security systems such as OTP (One Time Password) that are sent via SMS, WA and Voice have met the TFA (Two Factors Authentifications) standards are considered to still have a susceptibility to hijacking fraud account because often the OTP code is not sent to Users within a certain time limit. At present each domestic cellular operator has developed a Security System Verification and Authentification using API API connection between Merchant Applications and Users Handset (Smartphone) Users and Databases on Cellular Operators, this service is known as Phone Number Verification better so that it can meet the MFA (Multi-Factor Authentifications) standards.